THE TENDENCY OF BILINGUAL EDUCATION IN MODERN SCHOOL IN KAZAKHSTAN - Temirbulatova, A.K.; Em, T.V. (Халықаралық ғылыми форум МАТЕРИАЛДАРЫ 6–8 сəуір, 2016)
This article deals with the tendency and role of bilingual education in modern school in Kazakhstan. Nowadays the interest in bilingual education grows in Kazakhstan. The purpose of such education is formation of the bilingual persons capable freely to carry out communicative operations in two languages in all without exception life situations. In comparison with many other countries where there is an acculturation of the personality, in Kazakhstan both languages are demanded and fully function.
Keywords: bilingual; education; multicultural; ethnic and cultural; билингвальный; образование; многокультурный; этнокультурный